The effect of steering tail fin on performance on double pillars hybrid vertical axis wind turbine (Sultan Wind Turbine V-4.5) - Erwin Erwin; Slamet Wiyono; Muhammad Iqbal; Hilmy Maulana Yusuf (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
One of the methods to increase the efficiency of wind turbines is to add directional fins so that the wind turbine faces and is in the same direction as the wind. The use of triangular fins will slightly increase the performance of wind turbines compared to rectangular and trapezoidal shapes. The most crucial factor is that the fin area is not less than 5% of the swept area on the turbine blades. And according to calculations and simulation data, the convex pentagonal shape generates the greatest power. While the tests conducted by P.R. Ebert et al, that a twin wing with a high wing angle shows a greater damping response than a single wing. The aim of this research is to optimize the performance of the Sultan V-4.5 wind turbine by adding guide fins. Simulation methods and design of directional fins were carried out to obtain the most suitable fin shape and size. By using an aspect ratio of 1.4, the distance from the center of gravity to the center axis of the turbine is reduced. Performance tests were carried out using fins with areas of 0.06 m2, 0.12 m2 and 0.22 m2. Twin fins are used, with a 30o angle between them, to reduce the oscillatory forces resulting from wind motion. Fin profiles with maximum force when exposed to wind at angles of 0°, 5°, 10°, 15°, 20°, 25°, and 30° were selected from the available profiles using Computer Fluid Dynamic analysis. To determine the most suitable structure and material for fins, simulate the topology optimization and material selection used. According to his findings, the isosceles and right-angled triangles, which produce forces of 0.91 N and 0.77 N respectively, are the strongest. PVC plates are the materials used. The results of this study indicate that 2 m/s wind speeds frequency, the type 3b fin designs are the best design according to performance tests. The end result, coefficient of power increases and power generates increases respectively 5 and 3.8 times the previous research.